Merkel cell polyomavirus DNA detection in lesional and nonlesional skin from patients with Merkel cell carcinoma or other skin diseases - Foulongne, V.; Dereure, O.; Kluger, N.; Molès, J.P.; Guillot, B.; Segondy, M. (British journal of dermatology (1951), 2010)
Summary Background  A novel polyomavirus, the Merkel cell polyomavirus (MCPyV), has recently been identified in Merkel cell carcinoma (MCC). Objectives  To investigate the specificity of this association through the detection, quantification and analysis of MCPyV DNA in lesional and nonlesional skin biopsies from patients with MCC or with other cutaneous diseases, as well as in normal skin from clinically healthy individuals. Methods  DNA was extracted from lesional and nonlesional skin samples of patients with MCC or with other cutaneous diseases and from normal‐appearing skin of clinically healthy subjects. MCPyV DNA was detected by polymerase chain reaction (PCR) and quantified by real‐time PCR. Additionally, the T antigen coding region was sequenced in eight samples from seven patients. Results  MCPyV DNA was detected in 14 of 18 (78%) patients with MCC, five of 18 (28%) patients with other skin diseases (P = 0·007) and one of six (17%) clinically healthy subjects. In patients with MCC, viral DNA was detected in nine of 11 (82%) tumours and in 10 of 14 (71%) nontumoral skin samples (P = 0·66). MCPyV DNA levels were higher in MCC tumours than in nontumoral skin from patients with MCC, and than in lesional or nonlesional skin from patients with other cutaneous disorders. Signature mutations in the T antigen gene were not identified in the two MCC tumour specimens analysed. Conclusions  High prevalence and higher levels of MCPyV DNA in MCC supports a role for MCPyV in tumorigenesis. However, the high prevalence of MCPyV in the nontumoral skin and in subjects without MCC suggests that MCPyV is a ubiquitous virus.